Digital Representation of a Conceptual Leather Puppet Character using Holographic Prism Glass - Maria Wahyuni; Media Anugerah Ayu; R Anhas; Christian H Pangaribuan (Faculty of Engineering and Technology, Sampoerna University, 2020)
Leather shadow puppet performances are slowly becoming isolated. They are no longer attracting the young generation towards its long duration and language complexity, inclusive of its incomprehensible storytelling and characters. To address this gap, this research utilized a descriptive qualitative method and mind map to transcribe and describe key concepts of both redesigning and avatar creation of leather shadow puppet character. The purpose of this study was to explore an alternative method in representing leather puppet performance by implementing a holographic prism glass technique. The digital representation of a leather puppet through a holographic prism glass medium is a manifestation of appreciating Indonesian cultural artwork in the modern era. The contribution of this study is to provide a more detailed explanation of a new manner in exploring and preserving the narrative and figure of the cultural heritage.